STUDENT-CENTERED LEARNING IN CONTEMPORARY EDUCATION - Ko`shkinova Aynash Garifulla Qizi; Khamitov Eldorbek Erkinovich (TADQIQOTLAR, 2026)
ABSTRACT: Student-centered learning has become one of the most influential approaches in contemporary education, responding to the growing demand for learners who are autonomous, critical, and adaptable. Unlike traditional teacher-centered instruction, student-centered learning places learners at the core of the educational process, encouraging active participation, self-directed learning, and responsibility for one’s own academic development. This article examines the concept of student- centered learning, its theoretical foundations, key principles, and educational benefits. Based on an analytical review of pedagogical theories and empirical research, the study provides an original academic discussion of how student-centered learning contributes to academic success, motivation, and lifelong learning skills. The findings indicate that student-centered learning is an essential component of modern education systems and plays a significant role in preparing students for the challenges of the contemporary world.